La dynamique démocratique de l’économie sociale - Sylvain Celle (Revue de la Régulation)
This thesis focuses on the historical dynamic of the social economy in French capitalism from the nineteenth century until today. Social economy organisations (cooperatives, mutual societies, associations, etc.) develop original rule systems within capitalist economies. One of the hypotheses is that democratic rules within these organizations play a determining role in the empowerment and differentiation of the social economy related to the rules of capitalism. To question this hypothesis, we develop an institutionalist approach to social economy. The research is based on a large historical survey, using mainly qualitative methods as in-depth case studies. This thesis contributes to deepening our historical and analytical knowledge of social economy. It also helps to demonstrate the role of democracy in the differentiation of some systems of rules in capitalist economies.